Product Design Education for Circular Economy - Vicente, José (2020)
Design has continually developed new approaches to find the most appropriate solutions to the growing environmental and social problems. At the same time higher education courses have tried to adapt their curricula accordingly. The most recently proposed model is circular economy. It reinforces the idea of a paradigm shift to a system of closed loops where there is no waste. This article develops a state of the art on the integration of sustainability in product design in higher education and its evolution to embrace circular economy. This analysis includes identifying past experiences, which contents are addressed, what methodologies are used, what type of approach (focused or dispersed) and what are the needs for teaching staff. This paper tries to identify gaps in order to purpose better solution for circular economy integration.